An initial investigation of the relationship between capital structure and firm performance among large (G7) construction companies: a conceptual framework - Masrom, Md Asrul Nasid; Eahwan, Norsyamimi; Alifiah, Mohd Norfian; Goh, Kai Chen; Mohamed, Sulzakimin (JARDCS, 2018)
Capital structure decision plays a vital role in examining firm performance. The relationship between capital structure and firm performance is one that has received considerable attention in the previous literature. In Malaysia, a substantial amount of research on the relationship between capital structure and firm performance solely focused on companies that are listed in main market of Bursa Malaysia mainly in plantation, and rarely focused on construction firms. Furthermore, as for to date, limited study explores on large construction companies in regards to technology, consumer product, finance, industrial products and trading or services. By considering this drawback, this study aims to investigate the relationship between capital structure and firm performance among construction companies in Malaysia. Several determinants of capital structure and firm performance of the companies listed on the Bursa Malaysia are defined. To achieve the research aim, this study developed a conceptual framework based on an extensive previous study and several hypotheses. The results will show the differences of the relationship among sectors and it also will determine the direction of the relationship between variables. This study will make several important contributions to the existing studies of capital structure by providing basic knowledge on the relationships capital structure and their firm performance in which increasing their competitiveness in the market and future business opportunities.